Comparative bioactivity profile of phospholipids from three marine byproducts based on the zebrafish model. Issue 9 (16th May 2022) - Xie, Dongxiao; Li, Peihai; Zhu, Yongqiang; He, Junwei; Zhang, Mengqi; Liu, Kechun; Lin, Houwen; Zhai, Hongbin; Li, Xiaobin; Ma, Yaohong
Abstract: Phospholipids (PLs) are important components of physiological metabolism in animals and plants, and they have been widely used in clinical treatment, cosmetics, and industry. With the development of marine resources, marine PLs rich in polyunsaturated fatty acids have attracted increasing attention. As important marine resources, shrimp heads (SH), codfish roe (CR), and squid gonads (SG) contain a high PL content. The antithrombotic, antistroke, anti‐inflammatory, pro‐angiogenic, and cardioprotective activities of PLs from SH, CR, and SG were evaluated and compared using the in vivo zebrafish model. The results showed that the PL extracts of SH, CR, and SG had significant biological activities, which lays a theoretical foundation for the development and utilization of PLs in marine byproducts in the future, providing a new choice for the prevention of inflammatory and cardiovascular diseases. Practical applications: In this experiment, phospholipids in seafood from different sources were extracted, and their biological activities were comprehensively evaluated and compared using the zebrafish model to lay a foundation for the development of cardiovascular drugs, health food, special medicinal food, and other effective components. The utilization of marine byproducts not only makes full use of resources, but it also protects the environment. Abstract : The antithrombotic, antistroke, anti‐inflammatory, pro‐angiogenic, and cardioprotective activities of phospholipids from shrimp heads, codfish roe, and squid gonads were comprehensively evaluated and compared using the zebrafish model. There were significant differences among these distinct phospholipids in activities. The results lay a foundation for the development of phospholipids in marine byproducts in the future.